Blame it on the community, immunize the state and the international agencies: An assessment of water supply and sanitation programs in India - Saravanan V. Subramanian (University of Bonn, Center for Development Research (ZEF), 2013)
National and international agencies focus on "on-site" water supply and sanitation interventions targeting households to share costs, and showcase their commitment to the MDGs. This paper reveals that "on-site" interventions in India have exposed millions to mass poisoning and drowned the country in sewage waters. While "on-site" interventions are favoured, they fail to consider the integrated nature of the water supply, sanitation and sewerage systems; and burden households with additional social and economic costs. Failures in the programs are often blamed on the communities, while immunising the approach of the development agencies that fail to consider the integrated water infrastructure.
Keywords: 330; MDGs; water infrastructure; governance; public health; South Asia